Hubungan Antara Stres Kerja Dengan Kemampuan Pengambilan Keputusan Pada Pilot TNI Angkatan Laut Ditinjau dari Jam Terbang - Tarigan, Albert Kencana; Tambunan, Darwin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The objectives of this study were (1) to determine the relationship of job stress with the ability to take a decision on the Pilot Indonesian Navy in terms of flight hours (2) to know there are differences in job stress in terms of flying hours on pilots Indonesian Navy and (3) to determine No differences in decision-making in terms of flight hours on a Indonesian Navy Pilot. The sample in this study using the entire population (total sampling) as many as 100 people. The data collection is done by using questionnaires. Variables used in this research is the stress of work as an independent variable (X1) and decision-making as the dependent variable (Y) and flying hours as an independent variable (X2). Data analysis techniques used in this research is to use a software program SPSS 17.0 for Windows. The results in this study show that: (1) variable job stress and decision-making variables negative significantly, (2) work stress variables not have difference to the flight hours, (3) decision-making variables that not have a difference to the flight hours.